Angiogenic potential of human platelet rich concentrates on dental pulp stem cells in an in Vitro Inflammation Model / Priyadarshni Bindal - Priyadarshni , Bindal (2017)
Background: Healing of inflamed dental pulp by stimulating angiogenesis forms the basis of dental pulp regeneration. Dental pulp vitality is paramount for tooth longevity and function. Dental pulp stem cells (DPSCs) are mesenchymal stem cell population present in cell rich zone of dental pulp and demonstrate multilineage differentiation potential in healthy and inflamed microenvironment. Platelet rich concentrates (PRCs), a concentrated suspension of growth factors (GFs) are recognised as promoters of tissue regeneration through their paracrine action. Recently, PRCs has been introduced in the field of oral-maxillofacial and implant dentistry as a treatment modality. However, its effect on DPSCs in inflamed microenvironment is poorly understood. The aim of this study was to gain an insight into the healing and angiogenic potential of two types of PRCs namely human platelet lysate (HPL) and platelet rich plasma (PRP) on DPSCs in an inflamed state. Objectives: Firstly, the mesenchymal properties of DPSCs isolated from human adult dental pulp were characterised. Secondly, optimal concentration of bacterial lipopolysaccharide (LPS) to induce inflammation in DPSCs was investigated, followed by determination of two types of PRCs to maintain viability and induce angiogenesis in DPSCs. Finally, we compared the effect of the optimized concentrations of PRCs to induce angiogenesis in DPSCs in inflamed state (iDPSCs). Methods: DPSCs were isolated from dental pulp tissue extirpated from healthy premolars of patients indicated for orthodontic extraction and were characterised for their mesenchymal characteristics. Next, LPS was used in different concentrations to induce inflammation in DPSCs. Following this, DPSCs were treated with different concentrations of HPL and PRP to investigate their effect on cell viability and angiogenic effect on DPSCs. Effect of all the treatments given to DPSCs were validated via cell viability assay, gene expression analysis as well as analysis at protein level. Capacity of DPSCs to form tube-like structures after PRCs treatment was investigated by matrigel based functional assay. Results: Isolated DPSCs demonstrated positive mesenchymal characteristics. LPS for 24 hours considered optimum to induce inflammation in isolated DPSCs as evidenced by expression of pro-inflammatory markers at gene and protein level. 10%, 15%, 20% HPL and 5% PRP treatment on DPSCs maintained the cell viability and morphology, as compared to foetal bovine serum (FBS). It was noted that 20% HPL showed highest expression of angiogenic and cell adhesion surface markers, and capacity of DPSCs to form tube like structures. In iDPSCs, 20% HPL demonstrated significantly high cell viability and angiogenic potential. Conclusion: DPSCs could be induced to inflamed state by 1μg/mL LPS treatment for 24 hours. Viability of DPSCs was maintained in-vitro by 5% PRP, 10%, 15%, 20% HPL. Potential angiogenic effect on normal and inflamed DPSCs was demonstrated at 20% HPL. Clinical relevance: PRCs exhibit potential pro-angiogenic effect on DPSCs in inflamed state. Hence, they can be considered for potential pulp regenerative therapy in inflamed pulp.